2019
DOI: 10.1097/md.0000000000014173
|View full text |Cite|
|
Sign up to set email alerts
|

Association between tea consumption and gastroesophageal reflux disease

Abstract: Background:Gastroesophageal reflux disease (GERD) is one of the most common digestive system diseases, which is associated with lifestyle and dietary factors. The main mechanism involved in GERD is affected by demographics, lifestyles, and dietary factors. Tea consumption is reported to be associated with GERD, especially in Asian population. However, the effect of tea drinking on GERD risk is still controversial. The aim of this study was to investigate the relationship between tea consumption and the risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
2
10
0
2
Order By: Relevance
“…Therefore, we speculate that the improvement of constipation and diarrhea may be related to this mechanism. Re ux is a relatively common symptom in patients with esophageal cancer after surgery (Lagergren et al 2021), but no association was found between postoperative tea consumption and re ux in this study, which is consistent with the ndings of Cao et al (Cao et al 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we speculate that the improvement of constipation and diarrhea may be related to this mechanism. Re ux is a relatively common symptom in patients with esophageal cancer after surgery (Lagergren et al 2021), but no association was found between postoperative tea consumption and re ux in this study, which is consistent with the ndings of Cao et al (Cao et al 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we speculate that the improvement of constipation and diarrhea may be related to this mechanism. Reflux is a relatively common symptom in patients with esophageal cancer after surgery [27], but no association was found between postoperative tea consumption and reflux in this study, which is consistent with the findings of Cao et al [28]. In conclusion, we can speculate that tea drinking mainly improves the problems of eating and swallowing in postoperative esophageal cancer patients, and does not provide significant relief for symptoms such as reflux and nausea and vomiting.…”
Section: Discussionsupporting
confidence: 88%
“…Even though caffeine and theobromine have been suspected as some of the ingredients for heartburn, so far no clinical trials have been performed to definitively demonstrate that removing such foods from diet leads to the relief of GERD symptom [31]. Some of the newest researches even concluded that there was no significant relationship between tea consumption and the risk of GERD [32,33]. However, our CATA data revealed that some respondents indeed perceived certain level of "Heartburn" (stomach uncomfortableness) after drinking some of the tea infusions, and the fully-fermented SML and unfermented BLC were positioned closest to "Heartburn" on Figure 3.…”
Section: The Postprandial Perceptions Elicited In Young Taiwanese Consumers By Tasting the Taiwanese Specialty Tea Infusionsmentioning
confidence: 99%